2004
DOI: 10.1101/gad.1160904
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB RelA opposes epidermal proliferation driven by TNFR1 and JNK

Abstract: NF-B inhibition promotes epidermal tumorigenesis; however, whether this reflects an underlying role in homeostasis or a special case confined to neoplasia is unknown. Embryonic lethality of mice lacking NF-B RelA has hindered efforts to address this. We therefore generated developmentally mature RelA −/− skin. RelA −/− epidermis displays hyperplasia without abnormal differentiation, inflammation, or apoptosis. Hyperproliferation is TNFR1-dependent because Tnfr1 deletion normalized cell division. TNFR1-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
123
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 35 publications
17
123
1
Order By: Relevance
“…For example, one report demonstrated that inhibition of NF-kB in skin leads to oncogenic potential and potentiates H-Rasinduced transformation (Dajee et al, 2003). One mechanism to explain this concept is that inhibition of NF-kB in the skin leads to JNK activation (Zhang et al, 2004), a finding consistent with several reports that NF-kB activation suppresses the phosphorylation and activation of JNK.…”
Section: Nf-jb As a Tumor Suppressorsupporting
confidence: 74%
“…For example, one report demonstrated that inhibition of NF-kB in skin leads to oncogenic potential and potentiates H-Rasinduced transformation (Dajee et al, 2003). One mechanism to explain this concept is that inhibition of NF-kB in the skin leads to JNK activation (Zhang et al, 2004), a finding consistent with several reports that NF-kB activation suppresses the phosphorylation and activation of JNK.…”
Section: Nf-jb As a Tumor Suppressorsupporting
confidence: 74%
“…p65/RelA Ϫ/Ϫ, TNFR Ϫ/Ϫ epidermis lacked hyperplasia and displayed normal levels of CDK4 (Zhang et al, 2005) and JNK (Zhang et al, 2004). Pharmacological treatment of p65/RelA-deficient epidermis with a topical JNK inhibitor decreased levels of activated JNK and reversed the epidermal hyperplasia (Zhang et al, 2004). Together, these findings indicate that NF-B opposes the pro-liferative activity of TNFR1/JNK during epidermal development (see Fig.…”
Section: Nf-b-on the Same Team As Notchmentioning
confidence: 78%
“…Mouse epidermis and E14.5 keratinocytes deficient for p65/RelA display marked hyperplasia/proliferation, increased levels of active, nuclear c-jun NH 2 -terminal kinase (JNK1/2), and a significant increase in protein levels of cyclin-dependent kinase 4 (CDK4) (Zhang et al, 2004(Zhang et al, , 2005. JNK, a member of the MAP kinase family, is activated by tumor necrosis factor cell surface receptor, TNFR1 (as is NF-B), and participates in numerous cellular processes, including proliferation (reviewed in Aggarwal, 2000;Ghosh and Karin, 2002).…”
Section: Nf-b-on the Same Team As Notchmentioning
confidence: 99%
See 2 more Smart Citations